Biosensors for real‐time monitoring of physiological processes in the musculoskeletal system: A systematic review. Issue 12 (6th May 2019) - Veronesi, Francesca; Tschon, Matilde; Visani, Andrea; Fini, Milena
Abstract: Biosensors are composed of (bio)receptors, transducers, and detection systems and are able to convert the biological stimulus into a measurable signal. This systematic review evaluates the current state of the art of innovation and research in this field, identifying the biosensors that in vitro monitor the musculoskeletal system cellular processes. Two databases found 20 in vitro studies, from January 1, 2008 to December 31, 2017, dealing with musculoskeletal system cells. The biosensors were divided into two groups based on the transduction mechanism: optical or electrochemical. The first group evaluated osteoblasts or mesenchymal stem cell (MSC) biocompatibility, viability, differentiation, alkaline phosphatase, enzyme, and protein detection. The second group detected cell impedance, ATP release, and superoxide concentration in tenocytes, osteoblasts, MSCs, and myoblasts. This review highlighted that the in vitro scenario is still at an early phase and limited for what concerns both the type of bioanalyte and for the type of system detector used. Abstract : The systematic review identified the biosensors that in vitro monitor the musculoskeletal system cellular processes; 20 in vitro studies, from 2008 to 2017, were found; the biosensors were divided into optical or electrochemical.